STUDIES ON THE PERFORMANCE OF 'OVATIDE' - ON BREEDING OF INDIAN MAJOR CARPS - DUTTA, NARESH C.; MISHRA, SIDDHARTHA S.; PRADHAN, PRASENJIT; CHAKARABORTY, SUSANTA K. (Journal of Indian Fisheries Association, 2015)
The paper deals with the experimental studies on breeding of IndianMajor Carps- Catla catla (Valenciennes), Labeo rohita (Hamilton), Cirrhinusmrigala (Hamilton), & Labeo calbasu (Hamilton) with the help of 'Ovatide'which is being used as an alternative inducing agent for commercial seedproduction. This study has been conducted for six consecutive months (April-September, 2000) in a stone-pitched breeding channels of a farm located atMidnapore District, West Bengal. The doses of 'Ovatide' (0.5 mllkg of fishweight) remained same for each female species during the entire study periodand males were released without any dose. The physicochemical parametersof water during different months were estimated. The latency period andfertilization percentage varied in different months and species. The resultsconfirmed that 'Ovatide' can be used successfully in a much more cost-effectiveway for induced breeding of carps, even in rural fish farms with morrumpitchedbreeding channels.Keywords : Induced breeding, Indian Major Carps, Ovatide